Challenges and Problems in Implementing Effective Communication within Religious Missionary Activities Today - Widia Ningsih; Tukma Triputri Daulay; Muhammad Fadlan Anshori (Hikmah, 2025)
The primary objective of this study is to identify and analyze various communication problems that commonly arise in the implementation of religious missions, both in internal and external contexts. This research also aims to formulate relevant solutions and recommendations to enhance the effectiveness of communication in religious outreach or missionary activities. The focus of the study is not only limited to cross-cultural communication challenges—such as language barriers, differences in values, and social norms—but also includes internal communication dynamics among mission actors or members of religious organizations. Internal communication problems often become a source of misunderstanding, conflicts of interest, and lack of synergy, which ultimately hinder the achievement of mission goals. Therefore, this study emphasizes the importance of adopting inclusive, adaptive, and contextual communication approaches, especially within multicultural and pluralistic societies. The findings reveal that by implementing innovative, flexible, and empathy-based communication strategies, religious organizations can expand their audience reach and deliver religious messages more persuasively and meaningfully. This approach also has the potential to minimize conflict and increase acceptance of religious messages across diverse segments of society.